the Intelligent care. the wisdom of Florence Nightingale in the technological era. Merging care, innovation and humanity. (Salud, Arte y Cuidado, 2024)
As part of the celebration of International Nursing Day, we held at our “Universidad Centroccidental Lisandro Alvarado” the International Days: “Intelligent Care. The Wisdom Of Florence Nightingale In The Technological Era”. Focusing our gaze on the complex challenges facing modern nursing today: the increase in population, the diversity of illnesses and the need for personalized care. In this context, technology presents itself as an indispensable ally, our professional history tells us that it is in the 19th century, with the work of Florence Nightingale, known as the “Dama de la Lámpara”, who changed nursing and the world of her Health, for future generations, his legacy is undeniable, establishing fundamental practices that have lasted over time. Her focus on hygiene, humanized care and comprehensive patient care provided the basis for the profession, based on human values ​​that Nightingale impetuously defended. On the threshold of the digital era, nursing finds itself at a turning point where technology, with its disruptive potential, rises as a beacon of hope to improve human health. But how can we ensure that technological innovation does not deprive us of the human values ​​that Florence Nightingale defended with passion?Technology offers us powerful tools: from clinical information systems to mobile applications for patient monitoring. But its true impact is radical, as we integrate it into our daily practice. The technology can help us detect patrons in large data sets, optimizing decision making. Telehealth allows us to reach patients in remote areas. However, we must remember that these tools are average, not fine in themselves. In the digital age, we find ourselves faced with a unique opportunity: to merge Nightingale's wisdom with the technological tools available to further improve human care. The convergence of Florence Nightingale's wisdom and modern technology is our golden opportunity. It's not just about data and algorithms, it's about hearts and hands that care. Digital nursing must be a bridge between tradition and innovation, where technology amplifies our humanity rather than replacing it. Nursing in this category has the opportunity to combine the best of the past with the most innovative of the present. Let's follow the path brought by Florence Nightingale, adapting it to current needs. Therefore, we will achieve comprehensive care, where technology and humanity converge for the benefit of our patients.In honor of Florence Nightingale, let us continue moving forward with courage, embracing the digital era with the same passion, which she had behind the lamp, which illuminated her path. Our patients deserve the best of both worlds: science and heart. The “Dama de la Lámpara” on the ground changed the Nurse of her time; Her legacy lasts for a long time. Nightingale taught us that care goes beyond science and technology and that it is an act of compassion, empathy and human connection. In the digital age, we must keep her flame alive, infusing each mouse click with the same dedication, which she showed by turning on her lamp.This initiative in digital nursing, brought together a team from the UCLA Nursing Program in Barquisimeto, Lara Venezuela, marvelous and producer of new ideas, which achieved luxurious themes, with excellent lecturers and massive assistance, showing that, in the technological era, nursing continue preparing yourself in search of wisdom, with the gaze set on the light of Florence Nightingale's lamp, on your nighttime journeys in Crimea.